O Projektowaniu Konstrukcji z Uwzględnieniem Przystosowania w Przypadku, Gdy Stałe Sprężyste Zależą od Temperatury - König, J.A. (Engineering Transactions, 1972)
Melan’s theorem on the shake-down phenomena is generalized to the case of temperaturedependent elastic moduli. The new formulation of the theorem requires a suitable modification of the method of solution. In order to determine the regions of purely elastic behaviour of the structure the plastic stress-strain relations have been used. The numerical examples concerning rods, plates and thick-walled shells show the temperature sensibility of the Young modulus to be of the order of several percent.